Modern poetik och litterär konstnärlig forskning ur ett danskt-svenskt perspektiv - Quirin, Mia (Tidskrift för litteraturvetenskap, 2019)
Modern Poetics and Artistic Research in Literary Composition from a Swedish and Danish Perspective This article discusses how the first four Swedish dissertations in literary composition can be said to practice poetics. Poetics, understood as a modern, self-reflexive genre under the name of “author’s poetics,” has been subject to literary scientific research in Denmark that differs from comparable Swedish research, arguably due to the large number of Danish self-reflexive poetological works published since Paul La Cour’s Fragmenter af en dagbog (1948). The literary dissertations are situated on the border between composition and self-reflection in ways similar to the Danish authors’ poetics, but they are also closely connected to disciplinary poetics and traditional academic writing. The article therefore suggests that the literary dissertations can be said to create a new poetological spectrum, described as a disciplinary form of authors’ poetics.